Implementation of the Inquiry Model in Islamic Cultural History Learning at Islamic Junior High Schools in Sidikaling Subdistrict - Kesumawati, Leni; Qorib, Muhammad; Lubis, Rahmat Rifai (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This research focuses on the application of the inquiry learning model in learning Islamic Cultural History at MTs in Sidikalang sub-district. The problem faced is the low involvement of students in learning history who tend to be passive, where the learning model used still focuses on lectures and memorization, without providing space for critical thinking and connecting material with everyday life. This study aims to describe the implementation of the inquiry model, identify supporting and inhibiting factors, and explore the experiences of teachers and students in this learning. The research used a qualitative approach with case study method, involving in-depth interviews, observation, and documentation as data collection techniques. The results showed that the application of the inquiry model in MTs in Sidikalang sub-district has improved students' critical thinking skills, independence, and self-confidence. However, challenges such as time constraints, inadequate resources, and students' difficulties in formulating relevant questions remain obstacles. Nevertheless, the inquiry model has succeeded in creating more dynamic and relevant learning. This study concludes that the application of the inquiry model is effective in improving the quality of learning and can be applied optimally with adequate support.